STRATEGI PENGEMBANGAN SDM PENDIDIK UNTUK MENANGGULANGI KRISIS LITERASI DAN NUMERASI DI ERA KURIKULUM MERDEKA - Muhammad Ilzamul Khoir; Rahmat Shulhani; Misbahul Arifin; Achmad Fais Ghozali; Hendi Kurniyawan; Muhammad Zaki Maulana (STKIP Pesisir Selatan, 2026)
This study focuses on the human resource development strategy for educators in addressing the literacy and numeracy crisis in the Merdeka Curriculum era. Three variables studied were internal training, teacher community collaboration, and the use of the Merdeka Mengajar platform. The study used a quantitative approach with an explanatory design, conducted at MA Nurul Jadid Probolinggo with a population of all teachers. The sampling technique used total sampling if the number of teachers was less than 50, or proportional random sampling if larger. The research instrument was a questionnaire based on a Likert scale (1-5), while data analysis was carried out using multiple linear regression using partial tests (t-test) and simultaneous tests (F-test). The results showed that internal training had no significant effect on teacher literacy and numeracy competencies (Sig. = 0.551 > 0.05). In contrast, teacher community collaboration (Sig. = 0.000 < 0.05; t = 4.375) and utilization of the Merdeka Mengajar platform (Sig. = 0.005 < 0.05; t = 3.005) were shown to have a positive and significant effect. Simultaneously, all three variables significantly influenced teacher competency (Sig. = 0.000; F = 55.063). This finding indicates that improving teacher competency is more effective through professional collaboration and the use of educational technology, compared to relying solely on conventional in-house training.